ANALISIS PENGARUH IHSG, INFLASI, JUB, DAN KURS TEHADAP NILAI AKTIVA BERSIH REKSADANA BNI-AM DANA PENDAPATAN TETAP DOMPET DHUAFA PERIODE 2019-2023 - Azzahra, Firstania Nayla; Irmatussa’adah (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
The research is expected to provide information on how the IHSG, inflation, JUB, and exchange rates have significant effects on the NAB of the BNI-AM Dana Pendapatan Tetap Dompet Dhuafa mutual fund. Secondary data such as official statistics and previous research findings are used as quantitative analysis materials in this study. This research utilizes the Eviews software by applying the multiple linear regression method. Based on the test results conducted, it was found that the IHSG and inflation variables do not significantly affect the NAB of the Sharia mutual fund, while the JUB and exchange rates significantly influence the net asset value of the Sharia mutual fund. Keywords: IHSG, Inflation, Money Supply, Exchange, Net Asset Value